ESCO market in Turkey: Challenges and Opportunities - (:unkn) unknown (IEEE, 2015)
Energy demand in Turkey has grown, driven by population growth, industrialization, and urbanization. When increasing oil prices and restrictions brought to carbon dioxide emissions, are considered it is mandatory to increase efficiency of current resources, tending towards domestic and renewable energy resources. ESCOs are creating opportunities for reducing energy demand, controlling CO2 emissions and energy efficiency market. In this study, the market for ESCO services in Turkey is investigated. The ESCO market for Turkey is compared member states of European Union (EU) as a candidate country.
Keywords: Energy Service Companies; European Union; Turkey; RENEWABLE ENERGY; SERVICES